2004
DOI: 10.1038/sj.mp.4001548
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell dysfunction in schizophrenia indicated by increased S100B in the CSF

Abstract: assessment. On the other hand, the main weakness is that we assessed the suicidal attempters but not suicide completers.In conclusion, given the relatively small sample size of the suicide attempter group in this study, larger samples are needed in future investigations of the TPH2 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(56 citation statements)
references
References 10 publications
3
51
0
1
Order By: Relevance
“…7 The assumption of such extracerebral origins of altered S100B levels in schizophrenia is challenged by findings of elevated S100B in cerebrospinal fluid and postmortem brain tissue. 8,9 However, glial abnormalities in S100B release may also be caused by disrupted energy supply, as suggested by earlier cell culture studies. 2 Accordingly, impaired insulin signaling has been observed in the dorsolateral prefrontal cortex of schizophrenic patients.…”
mentioning
confidence: 74%
“…7 The assumption of such extracerebral origins of altered S100B levels in schizophrenia is challenged by findings of elevated S100B in cerebrospinal fluid and postmortem brain tissue. 8,9 However, glial abnormalities in S100B release may also be caused by disrupted energy supply, as suggested by earlier cell culture studies. 2 Accordingly, impaired insulin signaling has been observed in the dorsolateral prefrontal cortex of schizophrenic patients.…”
mentioning
confidence: 74%
“…Various reports have revealed that altered density and genes due to expressions of astrocytes are strongly related to schizophrenia. 34 For example, astrocyte has a protein called S100B, of which there is a significant amount in schizophrenia patients, 35 which makes astrocyte a promising biomarker to predict first episode schizophrenia in the future. 36 Therefore, glial cells have become a major source to supply pathophysiological significance and possible therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Aufgrund der Typ-1-Typ-2-Polarisierung bei Schizophrenie erwartet man im ZNS eine verstärkte Aktivierung von Astrozyten und eine Hemmung der Mikrogliafunktion. Dies zeigt sich in Form von erhöhten Spiegeln von S100B -ein Marker der Astrozytenaktivierung -im Serum und im Liquor schizophrener Patienten, unabhängig vom Medikationsstatus [63,64]. Eine Mikrogliaaktivierung, die bei weniger als 10% schizophrener Patienten zu finden ist, wird als Medikationseffekt diskutiert [3]; vielmehr scheint eine Mikrogliadegeneration bei Schizophrenie mit der Astrozytenaktivierung zu korrespondieren [83].…”
Section: Antipsychotika Rebalancieren Das Typ-1-/typ-2-ungleichgewichtunclassified